2016
DOI: 10.1063/1.4960204
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid waveguide-bulk multi-path interferometer with switchable amplitude and phase

Abstract: We design and realise a hybrid interferometer consisting of three paths based on integrated as well as on bulk optical components. This hybrid construction offers a good compromise between stability and footprint on one side and means of intervention on the other. As experimentally verified by the absence of higher-order interferences, amplitude and phase can be manipulated in all paths independently. In conjunction with single photons, the setup can, therefore, be applied for fundamental investigations on qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…5,65 Bend loss could be also reduced by scanning the WG track multiple times in all curved segments due to the tighter confinement of the modes caused by multiscan-induced large refractive index contrast. 66 Recently, Tan et al reported that the WG size can be controlled by adjusting the scanning passes [Figs. 6(a)-6(c)].…”
Section: Multiscanmentioning
confidence: 99%
“…5,65 Bend loss could be also reduced by scanning the WG track multiple times in all curved segments due to the tighter confinement of the modes caused by multiscan-induced large refractive index contrast. 66 Recently, Tan et al reported that the WG size can be controlled by adjusting the scanning passes [Figs. 6(a)-6(c)].…”
Section: Multiscanmentioning
confidence: 99%
“…Development of optical integrated and fibre technology has enabled construction of multiports [8] and hence multiarm interferometers [9,10]. The integrated multiports are realised as directional couplers with arms expanding in two or three dimensions [11,12,10]. The principal feature of a directional coupler is the proximity of waveguides in its central region which allows for efficient transfer of energy between them.…”
Section: Introductionmentioning
confidence: 99%
“…In order to access the required amplitude combinations, each path can be individually blocked by mechanical shutters. Compared to free-space setups [17] or partially integrated solutions [27], the present setup provides much better phase stability, which is a prerequisite to obtain meaningful results. For an in-depth analysis of potential systematic errors, which would bias a Peres test with single photons, we probed the interferometer with bright coherent light with negligible shot noise.…”
Section: Introductionmentioning
confidence: 99%